Identification and Validation of a Novel Locus Controlling Spikelet Number in Bread Wheat (Triticum aestivum L.) - Li, Tao; Deng, Guangbing; Tang, Yanyan; Su, Yan; Wang, Jinhui; Cheng, Jie; Yang, Zhao; Qiu, Xuebing; Pu, Xi; Zhang, Haili; Liang, Junjun; Yu, Maoqun; et al. (Frontiers in Plant Science, 2021)
Spikelet number is an important target trait for wheat yield improvement. Thus, the identification and verification of novel QTL/genes controlling spikelet number are essential for dissecting the underlying molecular mechanisms, and hence for improving grain yield. In present study, we constructed a high-density genetic map for the Chuanmai42/Kechengmai1 doubled haploid (DH) population using 13068 SNP markers from the Wheat 55K SNP array. A comparison between the genetic and physical maps indicated high consistence of the marker orders. Based on this genetic map, a total of seven environmentally stable QTLs associated with total spikelet number per spike (TSN) and fertile spikelet number per spike (FSN) were detected on chromosomes 2DL, 3DL, 4DS, 5AL and 7DS in five environments. Of these, the QTL, QTsn/Fsn.cib-3DL (PVE=5.97-22.91%, LOD=3.73-18.51), is probably a novel locus located in a 4.5 cM interval on chromosome arm 3DL flanked by the markers AX-110914105 and AX-109429351. This QTL was further validated in other two populations with different genetic backgrounds using the closely linked Kompetitive Allele Specifc PCR (KASP) marker KASP_AX-110914105. The results indicated that QTsn/Fsn.cib-3DL significantly increased the TSN (5.56-7.96%) and FSN (5.13-9.35%). In addition, significant correlations between TSN, FSN and grain number per spike (GNS) was also detected. These results provide valuable information for future precise mapping and cloning of QTsn/Fsn.cib-3DL.